Distributed Learning in British Columbia: A Journey from Correspondence to Online Delivery - Tim Winkelmans; Barry Anderson; Michael Barbour (Flexible Learning Association of New Zealand, 2011)
Kindergarten to Year 12 distance education began in Canada in British Columbia, around 1919. This fi rst distance education was by correspondence. Canada's fi rst online learning also began in British Columbia, about 15 years ago. Distance education and online learning have continued to grow in British Columbia as a result of geographic and demographic factors. This article describes the development and regulation of K-12 distance education in British Columbia, and the lessons drawn from this history that could be used in other jurisdictions.